Harrison's nephrology and acid-base disorders 2026-02-16T06:08:13+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Harrison, Tinsley Randolph, 1900-1978; Jameson, J. Larry; Loscalzo, Joseph (McGraw-Hill Education/Medical, 2013)

(untitled)
Featuring a compilation of chapters related to kidney function that appear in Harrison's Principles of Internal Medicine, Eighteenth Edition, this concise, full-color clinical companion delivers the latest knowledge in the field backed by the scientific rigor and authority that have defined Harrison's. You will find content from renowned editors and contributors in a carry-anywhere presentation that is ideal for the classroom, clinic, ward, or exam/certification preparation. Complete coverage of a broad spectrum of topics, including acid-base and electrolyte disorders, vascular injury to the kidney, and specific diseases of the kidney. Integration of pathophysiology with clinical management. 41 high-yield questions and answers drawn from Harrison's Principles of Internal Medicine Self-Assessment and Board Review, 18 edition. Content updates and new developments since the publication of Harrison's Principles of Internal Medicine, 18 edition, with 22 chapters written by physicians who are recognized experts in the field of nephrology and acid-base disorders. Helpful appendix of laboratory values of clinical importance